2019
DOI: 10.3762/bjoc.15.183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of optimal fluorescent probes for G-quadruplex nucleic acids through systematic exploration of mono- and distyryl dye libraries

Abstract: A library of 52 distyryl and 9 mono-styryl cationic dyes was synthesized and investigated with respect to their optical properties, propensity to aggregation in aqueous medium, and capacity to serve as fluorescence “light-up” probes for G-quadruplex (G4) DNA and RNA structures. Among the 61 compounds, 57 dyes showed preferential enhancement of fluorescence intensity in the presence of one or another G4-DNA or RNA structure, while no dye displayed preferential response to double-stranded DNA or single-stranded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…In contrast, the very low emission intensity of 3d did not change upon the addition of ct DNA. The fluorescence light-up effects of the ligands 3a-c upon association with DNA resembled the ones observed for other styryl-substituted quinolizinium derivatives [62][63][64][65][66][67]. Accordingly, the emission enhancement most likely resulted from the accommodation of the ligand in the constrained binding site of the DNA, which led to a restricted conformational flexibility.…”
Section: Dna-binding Propertiesmentioning
confidence: 56%
See 1 more Smart Citation
“…In contrast, the very low emission intensity of 3d did not change upon the addition of ct DNA. The fluorescence light-up effects of the ligands 3a-c upon association with DNA resembled the ones observed for other styryl-substituted quinolizinium derivatives [62][63][64][65][66][67]. Accordingly, the emission enhancement most likely resulted from the accommodation of the ligand in the constrained binding site of the DNA, which led to a restricted conformational flexibility.…”
Section: Dna-binding Propertiesmentioning
confidence: 56%
“…As the quinolizinium ion has been established as a versatile platform for the development of DNA intercalators [60], we identified styryl-substituted quinolizinium derivatives as a promising basis for the search for photoswitchable DNA binders based on the photocycloaddition-photocycloreversion equilibrium. In fact, some selected styrylquinolizinium derivatives have already been shown to bind to DNA [61][62][63][64][65][66][67], however, their photocycloaddition reaction and the propensity of the corresponding photodimers to release the DNA-binding ligand have not been reported so far. Herein, we report on the photochemical and DNA-binding properties of the selected styrylquinolizinium derivatives 3a-d and demonstrate their ability to operate as photoswitchable DNA ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this chemosensor and derivatives thereof have the potential to be applied for the fluorimetric detection of pH gradients and extracellular nucleic acids in biofilms, [31] that have been suggested just recently to contain G4‐DNA as functional component [60] . Although numerous fluorescent probes for G4‐DNA are known, [9–19] to the best of our knowledge, no examples have been reported so far with these particular features. Namely, only a few fluorescent probes for G4‐DNA have been reported that operate at lower pH, [61] but these probes do not exhibit the dual‐mode response of compound 3 a .…”
Section: Discussionmentioning
confidence: 99%
“…For an efficient detection, however, either the emission intensity of the otherwise non‐fluorescent ligand has to increase strongly or the emission energy has to shift distinctly. Thus, several organic fluorophores have been introduced that serve this purpose, for example benzimidazole, [9] benzindole, [10] triazine, [11] coumarin, [12] cyanine, [13] pyridinium, [14,15] quinolinium, [15,16] quinolizinium, [15,17] triangulenium [18] and benzothiazole [19] based dyes. Among the promising compound classes for this application are also DNA‐binding natural products with suitable fluorescence properties, because these compounds usually provide sufficient affinity, and often selectivity, towards DNA, along with the required biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation